Pattern, severity, and treatment outcomes in acute poisoning patients admitted to the Saint Peter Specialized Hospital Toxicology Center in Addis Ababa, Ethiopia, 2023: a retrospective study - Kebede, Yared Negussie; Mohammed, Abdurehman Seid; Menberu, Chekole Sileshi; Mekete Diress, Getachew (Frontiers in Toxicology, 2025)
BackgroundPoisoning is a global public health problem that has more unfavorable outcomes in developing countries. This study aimed to assess treatment outcomes and associated factors among poisoned patients treated at Saint Peter Specialized Hospital Toxicology Center.MethodsAn institutional-based retrospective cohort study was employed by reviewing medical chart records of acutely poisoned patients who had been admitted at St. Peter Specialized Hospital Toxicology Center on 01/01/2017 to 30/12/2023 and the medical chart records review was employed from 01/01/2024 to 30/01/2024. This study analyzed records of 553 poisoned patients. A systematic random sampling technique was used to select the study unit. Data were entered and analyzed using Statistical Package for Social Sciences (SPSS) Windows version 26. A binary logistic regression model was used to identify associated factors for treatment outcomes of poisoned patients. A p-value <0.05 was considered statistically significant.ResultA total of 553 documents of poisoned patients were assessed. The overall mortality rate was 18 (3.25%), and four patients developed chronic complications. Factor analyses show that arrival to the center before 4 h (AOR = 0.43, P = 0.008) predicted recovery, whereas arrival at the toxicology center after 8 h (AOR = 2.21, P = 0.004), being hypotensive (AOR = 1.85, P = 0.002), needing intubation (AOR = 2.52, P = 0.014), and the presence of two or more complication (AOR = 3.3, P < 0.001) at admission were predictors of mortality.Conclusion and RecommendationThe mortality rate for poisoned patients was 18 (3.25%). In this study, delayed arrival to the toxicology center, being hypotensive, needing intubation, and the presence of two or more complications at admission were factors associated with the mortality and morbidity of the patients. Establishing a strong referral link between the toxicology center and regional health institutions, ensuring the availability of possible advanced clinical setup early recognition, and aggressively resuscitating critically ill patients will help minimize unfavorable outcomes.